KETIKA PARADIGMA POSITIF MENDAMPINGI PARADIGMA NON-POSITIF DALAM RISET AKUNTANSI - Mohamad Suyunus (EKUITAS (Jurnal Ekonomi dan Keuangan), 2012)
On the last Accounting National Symposium at Banjarmasin, a quantitative accounting research approach was still dominating in the paper presentation, eventhough this event had been conducted more than a decade. So, why the quantitative approach or positive paradigm is still strong enough in its position and having a good track of development during the penetration of a qualitative approach? By understanding the positivist accounting researcher’s thought about qualitative approach, a gap could be seen and then used for developing both approaches simultaneously. This research is on the area of an interpretive paradigm and using case study method. By using in-depth interview, data are collected from informan at Gadjah Mada University, Brawijaya University, and Airlangga University. The results, all informan accept the qualitative approach or a multiparadigm accounting research with a certain note, especially regarding to the research stages. Besides, they think about the need for a dialogue between quantitative and qualitative researchers.